Air dose rate to 137Cs activity per unit area ratio for different land use 7 years after the nuclear accident -Case of the slope catchment, Ogi reservoir, Fukushima. (September 2020) - Basuki, Triyono; Bekelesi, Wiseman Chisale; Tsujimoto, Masaya; Nakashima, Satoru
Abstract: In the Fukushima Daiichi Nuclear Power Plant (FDNPP) accident, a considerable amount of radioactive materials were released into the environment. Long-term monitoring is essential for radiation protection and decontamination of the environment. In this study, we analyze the ratio of the air dose rate to 137 Cs activity per unit area on the ground over different land use types, and further examine the factors that influence this ratio. It was found that the ratio was relatively higher for forest areas than that for open areas, which may have been caused by effect of continuous 137 Cs influx from the forest canopy for a while after the accident. The less influence of vertical migration to the ratio was shown, maybe because the soil shielding effect is negligible by considering more than 75% of 137 Cs is still in the surface soil. The ratio is expected to be relatively less changeable in the future, owing to the immobilization of 137 Cs in the soil after seven years. The ratio data can be used to estimate future air dose rates, based on the 137 Cs activity per unit area for long-term monitoring and evaluation of decontamination activities. Highlights: Air dose rate to 137 Cs activity per unit area ratio was evaluated. The ratio was higher in forests than in open areas. Effect of 137 Cs from forest canopy, 137 Cs vertical migration in soil and lapsed time was observed. Less changeable ratio for future dose assessment from 137 Cs was predicted.